2017
DOI: 10.3389/fphys.2017.00225
|View full text |Cite
|
Sign up to set email alerts
|

Modified Low-Dose Triiodo-L-thyronine Therapy Safely Improves Function Following Myocardial Ischemia-Reperfusion Injury

Abstract: Background: We have shown that thyroid hormones (THs) are cardioprotective and can be potentially used as safe therapeutic agents for diabetic cardiomyopathy and permanent infarction. However, no reliable, clinically translatable protocol exists for TH treatment of myocardial ischemia-reperfusion (IR) injury. We hypothesized that modified low-dose triiodo-L-thyronine (T3) therapy would confer safe therapeutic benefits against IR injury.Methods: Adult female rats underwent left coronary artery ligation for 60 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 54 publications
1
17
0
1
Order By: Relevance
“…Supplementation of T3 has not been proven to be effective in improving outcomes among patients with noncardiac illnesses-induced LT3S [23]. However, the effect of T3 replacement in patients with AMI [9,24] remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of T3 has not been proven to be effective in improving outcomes among patients with noncardiac illnesses-induced LT3S [23]. However, the effect of T3 replacement in patients with AMI [9,24] remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The lncrna H19 (H19) is located on human chromosome 11 and expresses a 2.3 kb lncrna transcribed from the maternal inherited allele (13). increased expression of H19 was detected in rats following surgically induced myocardial i/r, suggesting that H19 may have a role in the protective mechanisms against i/r injury (14). Previous studies have also indicated that H19 exerts protective effects against hypoxia-induced injury in cardiomyocytes (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, evidence is accumulating that TH administration post MI and HF improves cardiac contractility and myocardial remodeling, and improves cardiovascular risk factors, especially lipid profiles (12,13). It was recently demonstrated that T3 safely improved heart function and remodeling in experimental models of MI and ischemia-reperfusion injury (14,15). However, it has not been shown whether such a T3 treatment-monitoring protocol can serve as an efficient therapeutic strategy in comparison with existing standard therapies.…”
Section: Introductionmentioning
confidence: 99%